Assessment of Greenhouse Gases Emission in Smallholder Rice Paddies Converted From Anyiko Wetland, Kenya - Owino, Christine Nyagaya; Kitaka, Nzula; Kipkemboi, Julius; Ondiek, Risper Ajwang' (Frontiers in Environmental Science, 2020)
Rice is an important food crop in Kenya and it is ranked third most consumed cereal crop after maize and wheat. The amplified demand for rice has resulted to conversion of wetlands to rice paddies and increased use of fertilizer, thus reducing wetlands ability to carbon sequestration. Consequently, there is enhanced emission of three potent greenhouse gases (GHGs); methane (CH4), nitrous oxide (N2O) and carbon dioxide (CO2). This study assessed the impact of fertilizer application on GHGs emission and the nutrient stocks in rice paddies. The study was carried out from September 2018 to January 2019 in papyrus dominated wetland in Western Kenya. Sampling was done on a weekly basis for the first two months, and thereafter twice per month in Anyiko rice paddies located in river Nzoia basin, Kenya. Two replicates of three treatments; standard, control and under fertilization were assigned randomly in six plots. Static chamber method was used to collect GHGs and analysed by gas chromatography. Soil samples were collected and analysed for nitrogen and carbon stocks. There was no significant difference in carbon and nitrogen stocks among the three fertilization scenarios (One-way ANOVA, F (2,33)=0.219, P>0.05 for carbon and F(2,33)=0.134, P>0.05 for nitrogen). The amount of NO3-N and NH4-N were not significantly different across all the fertilization scenarios (Kruskal-Wallis, P>0.05). Kruskal-Wallis test (P>0.05) indicated that there was no significant difference in the mean fluxes of CH4 and CO2 among the three fertilization scenarios. However, for N2O the mean fluxes differed significantly (P<0.05). The mean fluxes indicated that under-fertilized plot was a probable sink for N2O (- 0.59±0.45 µgm-²h-¹) and a source for CH4 (6.93±2.42 mgm-²h-¹) and CO2 (208.81±36.20 mgm-²h-¹). Standard-fertilized plot was source for N2O, CO2 and CH4 (4.37±3.18 µgm-²h-¹, 248.29±41.22 mgm-²h-¹, 4.00±6.34 mgm-²h-¹,) respectively. The control plot acted as sink for N2O (-3.59±2.56 µgm-²h-¹) and a source for CH4 (8.30±4.79 mgm-²h-¹) and CO2 (174.80±26.81 mgm-²h-¹). In this study, different fertilization scenarios had positive effect on N2O emission but no effect on CO2 and CH4 emission and also on nutrient stocks.